(untitled) (Research, Society and Development, 2022)
The aim of this study is to verify what has been developed in the world scientific literature in project management practices (GP) and implementation of Project Management Office (EGP) in hospitals. This is an integrative literature review, with a final sample of 19 articles; the results were results regarding the year, place of study, best practices, tools and challenges. A search was also made for consonance between the findings and the typological functions developed and defended by Hill (2008), which make up the functions of an EGP; it can be seen that among the 19 selected articles, all present practices that permeate one of the 5 functions of HILL (2008). Thus, it is possible to conclude that the implementation of an EGP in hospitals is promising when considering national and international results.